THE INFLUENCE OF MACROECONOMIC DYNAMICS ON ECONOMIC GROWTH IN DEVELOPING G20 COUNTRIES - M. Wahyu Shihab; Sirojuzilam; M. Syafii (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study investigates the long-run and short-run effects of macroeconomic variables—inflation, interest rates, exchange rates, foreign direct investment (FDI), and government expenditure—on economic growth using annual panel data from nine developing G20 economies over the period 2000–2023. The Panel ARDL model with the Pooled Mean Group (PMG) estimator is applied to capture cross-country heterogeneity while ensuring consistent long-run estimates. Long-run results indicate that inflation (β=0.147; p<0.01), FDI (β=0.191; p<0.01), and government expenditure (β=0.390; p<0.01) positively and significantly affect GDP growth, whereas interest rates exert a negative impact (β=-0.249; p<0.01). Exchange rates show no significant long-run effect. In the short run, FDI (β=0.046; p<0.05) and exchange rate (β=0.876; p<0.01) significantly stimulate growth, while inflation shows marginal significance (β=0.044; p<0.10). The error correction term (β=-0.846; p<0.01) confirms rapid adjustment toward equilibrium. These findings highlight the importance of inflation stability, prudent monetary policy, FDI promotion, and efficient fiscal spending in sustaining economic growth across developing G20 countries.